Implementasi Fuzzy Logic Mamdani pada Sistem Monitoring dan Kontrol Kandang Maggot BSF - Irfan Harlim; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the successes in cultivating BSF (Black Soldier Fly) maggots is influenced by the quality of the environment that must remain ideal, namely temperature and humidity. But this is still rarely known so that it is one of the factors causing the failure to cultivate BSF maggots. Therefore, the monitoring and control system on the BSF maggot cage can be a solution to this problem. The telegram application serves as a media viewer of the designed system. Monitoring serves to get the latest information about the temperature and humidity in the BSF maggot cage, while the control system is designed to determine the active actuator according to the conditions in the BSF maggot cage to remain ideal using the fuzzy logic Mamdani method. From the test results it is concluded that the system can work according to its functions. Telegram bots can provide feedback according to commands sent by users with a response time of 2 seconds. The accuracy of the DHT22 sensor in temperature sensing is 99.16% while the accuracy in humidity sensing is 95.31%. The implementation of fuzzy logic in the system can make the quality of the BSF maggot environment remain ideal and can determine the active actuator according to the conditions on the BSF maggot cage with accuracy to the lamp defuzzification output of 99.89% and the accuracy to the mist maker and fan defuzzification output of 98.66%.